What do we know about the future of foresight modeling related to food systems? - Wiebe, Keith D.; Mosnier, Aline; Mason-D'Croz, Daniel; Petsakos, Athanasios; Svensson, Johannes; Zurek, Monika (International Food Policy Research Institute, 2025)
“Foresight modeling” is thinking about the future using a simplified representation of reality to inform choices we make today.